Intramolecular aurophilic interactions in dinuclear gold(i) complexes with twisted bridging 2, 2′-bipyridine ligands. Issue 36 (7th September 2021) - Shmelev, Nikita Y.; Okubazghi, Tesfu H.; Abramov, Pavel A.; Komarov, Vladislav Y.; Rakhmanova, Mariana I.; Novikov, Alexander S.; Gushchin, Artem L.
Abstract : Five new luminescent dinuclear gold(i ) complexes with an atypical twisted bridging 2, 2′-bipyridine ligand have been obtained and structurally characterized. The structures of these gold complexes have some similarities with a crab body. Abstract : Elimination of the chloride ion from the [(PPh3 )AuCl] complex using silver triflate (AgOTf) in the presence of 2, 2′-bipyridine R2 bpy (the Au : R2 bpy molar ratio is 2 : 1) in dichloromethane at room temperature leads to dinuclear gold(i ) complexes [(PPh3 Au)2 (μ-R2 bpy)](OTf)2 (R2 bpy = bpy (1 ), dbbpy (2 ), CH3 Obpy (3 ), 3-CO2 CH3 bpy (4 ), 4-CO2 CH3 bpy (5 )) in high yields. The crystal structures for all compounds were determined using X-ray diffraction analysis. In all structures, gold ions are in a typical linear environment, and the bipyridine molecule is twisted, which allows intramolecular aurophilic interactions. Relatively short Au(i )⋯Au(i ) contacts (3.1262 (2)–3.400 (1) Å) are found in structures 3–5 . DFT calculations show the presence of bond critical points (3, −1) for aurophilic interactions in these structures. In structures 1 and 2, the Au(i )⋯Au(i ) distances are noticeably larger and equal to 4.479 (1) and 4.589 (1) Å respectively; there are no bond critical points (3, −1) for aurophilic interactions. All complexes show photoluminescence in solid state at room temperature when excited at 300 nm in a wide spectral range: from blue or blue-green emission (400–460 nm) for 1–4 to orange emission (580 mn) for 5 . The lifetimes of the excited state are in the microsecond range which is characteristic of phosphorescence. TD-DFT calculations reveal that electronic transitions of different nature are responsible for the photoluminescence of these compounds.